2017
DOI: 10.3892/mmr.2017.7362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artesunate prevent nephritis via the Toll-like receptor 4/nuclear factor-κB signaling pathway in rats

Abstract: The active ingredient in Artemisia carvifolia, artemisinin, may alleviate inflammation and toxicity. Artemisinin and its derivatives are first‑line anti‑malarial drugs currently, which have rapid effects on fever caused by malaria parasites with fewer side effects. The present study investigated the effects of Artesunate in a mouse nephritis model. Mice were injected intraperitoneally with 500 µl pristine to induce nephritis, and were treated with 28.8 mg/kg Artesunate. Subsequently, proteinuria, renal functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…ART is widely used in clinical practice and is recommended by the World Health Organization for the treatment of malaria, especially for cerebral and falciparum malaria [16]. ART has been intensively investigated due to its potential functions involved in anti-tumor [4], immune regulation [5], inhibition of inflammation [6], and treatment of type I diabetes [7]. An animal model of subarachnoid hemorrhage has been established in our previous study, and the data revealed that ART could protect the blood-brain barrier by activating sphingosine 1 phosphate receptor 1/phosphatidylinositol 3 kinase (S1pR/PI3K) signaling pathway [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ART is widely used in clinical practice and is recommended by the World Health Organization for the treatment of malaria, especially for cerebral and falciparum malaria [16]. ART has been intensively investigated due to its potential functions involved in anti-tumor [4], immune regulation [5], inhibition of inflammation [6], and treatment of type I diabetes [7]. An animal model of subarachnoid hemorrhage has been established in our previous study, and the data revealed that ART could protect the blood-brain barrier by activating sphingosine 1 phosphate receptor 1/phosphatidylinositol 3 kinase (S1pR/PI3K) signaling pathway [8].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of endogenous NSPCs triggered by trauma or ischemia, is not sufficient enough to induce neural repair, which could contribute to permanent disability in stroke patients [3]. Artesunate (ART) is a watersoluble derivative of artemisinin, which has been intensively investigated due to its potential functions involved in anti-tumor [4], immune regulation [5], inhibition of inflammation [6], and treatment of type I diabetes [7]. Our previous study using an established animal model of subarachnoid hemorrhage revealed that ART could protect the blood-brain barrier AGING by activating sphingosine 1 phosphate receptor 1/phosphatidylinositol 3 kinase (S1pR/PI3K) signaling pathway [8].…”
Section: Introductionmentioning
confidence: 99%
“…For LN mice, it has been reported that treatment with ARSs could decrease interferon-gamma (IFN-g), tumor necrosis factor-alpha (TNF-a), interleukin-6 (IL-6) in serum, and blocked intercellular adhesion molecule-1 (ICAM-1), fractalkine, NF-kB signaling pathway in renal (Dong et al, 2003;Li et al, 2006;Wang et al, 2010;You et al, 2014;Liang et al, 2018). A similar effect was observed in the nephritis and septic AKI models Wan and Li, 2017;Liu et al, 2019). Also, ARSs were reported to inhibit disease progression via downregulating renal monocyte chemoattractant protein 1 (MCP-1) expression in LN, IgAN, and septic AKI models (Mi et al, 2009;Jin et al, 2009;Ma et al, 2009;Liu et al, 2019).…”
Section: In Vivomentioning
confidence: 79%
“…Artemisinins downregulated the levels of MMP2 and TIMP-2 whilst up-regulating E-cadherin in hepatocarcinoma cells lines ( Zhao, Zhang, Xu, & Wang, 2017 ). Artesunate has been shown to upregulate the expression of adhesion molecules integrin β1 and neural cell adhesion molecule (NCAM) in embryonal rhabdomyosarcoma cells, thereby reducing migration and invasion ( Wan & Li, 2017 ).…”
Section: Artemisinins: Effects On Tumour Cell Migration Invasion Andmentioning
confidence: 99%
“…The anti-inflammatory effects of artesunate have also been investigated in animal models of myocardial ischaemia, acute lung injury and nephritis ( Efferth et al, 2007 ; Liu et al, 2018 ; Wan & Li, 2017 ; Zhao et al, 2017 ). In a rat model of transient myocardial ischemia, artesunate conferred myocardial protection via inhibition of glycogen synthase kinase- 3β, inhibition of NF-κB, activation of endothelial NOS, activation of the STAT3 (SAFE) pathway and activation of the PI3K/Akt/ERK 1/2 (RISK) pathway ( Khan et al, 2018 ).…”
Section: Artemisinins: Modulation Of Key Inflammatory Pathwaysmentioning
confidence: 99%